Strategi Pemerintah Desa Karangagung dalam Mempertahankan Kemandirian Desa Pesisir - Triana Dianita Handayani; Mangihut Siregar; Aji Agus Wijoyo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The village government's strategy in maintaining Karangagung Village as an independent coastal village is a strategic issue in national development. Villages as a leading government unit have an important role in encouraging local economic growth, improving community welfare, and realizing sustainable development. This study uses a qualitative descriptive method to describe the optimal management of village potential by paying attention to economic, social, and environmental sustainability aspects. Karangagung Village has managed to show significant development with an increase in status based on the Building Village Index (IDM), from a developing village to a developed village in the 2018–2022 period, until it reached the status of an independent village. This success reflects the increasing capacity of the village government in managing resources, public services, and community empowerment. Village heads play a strategic role in formulating policies, mobilizing community participation, and empowering local potential, especially marine fisheries and salt ponds as strategic economic assets. Information technology innovations, such as the use of web-based applications for village budget management, have been proven to increase transparency, accountability, and governance efficiency. These findings confirm that sustainable natural resource management, community collaboration, and the use of information technology are the main factors in strengthening the independence of coastal villages.